Laparoscopic Cholecystectomy under Spinal Anaesthesia – A Single Center Experience - Gupta, Nikhil; Kathpaul, Rachan; Gupta, Arun Kumar; Yelamanchi, Raghav; Singh, Raj Pal; Durga, CK (Nepal Medical College Journal, 2021)
Traditionally, laparoscopic cholecystectomy is performed under general anaesthesia. However, it can be performed under spinal anaesthesia as the dissection is confined to the gall bladder fossa and cystic triangle and bowel handling is usually minimal. The present study was performed to study the feasibility of performing laparoscopic cholecystectomy under spinal anaesthesia. A prospective observational single center cohort study was conducted with a sample size of 60 patients diagnosed with gall stone disease. Laparoscopic cholecystectomy was performed under spinal anaesthesia using low insufflation pressure of 8-10 mm of Hg. The outcomes studied include intra operative events (hypotension, bradycardia, abdominal pain, shoulder pain and requirement for sedation), reasons for conversion (spinal to general anaesthesia and from laparoscopic to open cholecystectomy), post-operative pain and complications. Females were more commonly affected than males and at a younger age. Three cases were converted from spinal to general anaesthesia. Two cases were converted from laparoscopic to open cholecystectomy. Intra operative analgesia and sedation were required in 10% and 13.3% of patients respectively. In the post operative period majority of the patients did not require any analgesia. Complications like headache (3.3%) and low backache (5%) were managed conservatively. About 5% of patients required urinary catheterization for post operative urine retention. Laparoscopic cholecystectomy can be performed safely under spinal anaesthesia with minimum morbidity. Spinal anaesthesia involves less cost and is better in terms of post operative pain control. The incidence of various post operative complications are less and manageable.